Investigation of Line-Commutated Three-Phase Converters under Voltage Unbalance - Weiland, Manuel; Herold, Gerhard (International Conference on Renewable Energies and Power Quality ICREPQ '10, 2010)
Power converters operated in unsymmetrical three-phase electrical systems will generally work asymmetrically. This introduces disadvantages for the operation of the electrical power system, like non-characteristic harmonics. In the case of controllable power converters, such as thyristor converters, it is possible to operate the converter with asymmetrical firing angles. This offers the opportunity to react on the system’s unbalance optimizing the asymmetrical operation of the converter to lower the disadvantages. In this paper, a method is presented to calculate the behaviour of electrical equipment based on line-commutated current con- verters. Thereby, the operation of the essentially non-linear system is described as sectional continuous linear problem. For its solution an approach with differential equations in the range of space-phasors is used. It is shown to be possible to optimize the unsymmetrical operation with respect to certain quality criteria by using unsymmetrical firing angle
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.leen.invest
Keywords: Power converter; voltage unbalance; converter control; distortion; optimization